Analysis of the Role of Handicraft Production in Rural Sustainable Development: A Case of Sar Aqa Seyyed, Chaharmahal and Bakhtiari - Divandari, Javad; Danaeinia, Ahmad; Izadi, Parisa (Journal of History Culture and Art Research, 2017)
Prioritizing the Rural development is one of the fundamental concerns of the Islamic Republic of Iran that is not achieved only through the agriculture development in villages of Iran, since weakness of agricultural foundations affect the unstable ecological conditions including the shortage of agricultural fields and the lack of the increase in number of land plots under cultivation, and cannot provide the proper social and economic indices for rural development. Experiences of successful countries in the rural development show the importance of the village industrialization in creating the job opportunities and preventing the rural migration to the cities. Theory of development and industrialization of rural areas is a factor affecting the economic and social development process and may be considered as the last solution for solving the problem of poverty in the rural areas as we see its success in China through this paper. Therefore, this paper examines the role of the handicraft production in sustainable development in the Sar Aqa Seyyed village. A number of handicrafts including carpet weaving as the main handicrafts of Sar Aqa Seyyed village are still flourishing. Handicraft production and development in this village not only creates employment opportunities and income, but also can play a major role in sustainable development and the village independence.